História da educação rural na América Latina relações entre Brasil e México (1940-1950) - Silva, Rony Rei do Nascimento (Editora Oficina Universitária, 2022)
To write this book, I lived the experience of one year in a country where every day I was taught something about my research topic. In Mexico, I recognized my Latinity on a journey through its flavors, its history, the routine of its people and, above all, through the social inequalities that unite our countries. I won't forget the Potosino desert, the architectural curves of El Colsan, the indigenous woman who sold tortillas, the organilleros in Mexico City, Diego Rivera's murals at SEP, the bike ride to Unam... Mexico, I ate your food and drank your drink. I tasted the Rosca de Reyes served by Professor Oresta and the Tarasca soup on the shores of Lake Pátzcuaro, as well as the tragicomic experience of eating a habanera pepper that accompanied an order of tacos at the Vera Cruz carnival. Finally, I address the readers of this book as a young researcher who seeks his authorship in his own lived experiences and in contact with his peers.